Analysis of the Relationship Between Foreign Sea Transportation Visits and Gross Domestic Product Regional in the Processing Industry Sector - Rifansa, Aditya; Setiawan, Muhammad Ikhsan; Dwi Apriliani, Dora; Prasetijo, Joewono (Malikussaleh University, Aceh, Indonesia, 2023)
Sea transportation is also very much needed in the processing industry for ships and passengers and the flow of goods. Suppose the incoming ship can be seen as a sender of goods or the processing industry itself. This is supported very well by the cargo and costs for sea transportation, with much cargo at a relatively low cost. Analyzing the relationship of foreign sea transportation with the regional GDP of the processing industry sector. From ship visits consisting of total and units to passenger visits consisting of passenger arrivals and departure, for variable analysis using correlation and hypothesis testing. The results of overseas sea transportation with the GDP Regional the processing industry are for the correlation results of ship visits from units (0.613) with a strong and total correlation (0.596) with a moderate correlation, for passenger arrivals (0.262) and passenger departures (0.280) both have a low correlation relationship, for the unloading flow of goods (0.607) has a strong correlation. So the visits of foreign sea transportation ships with the GDP Regional of the processing industry sector have a significant relationship of (0.00) from the unit or total ships; for passenger visits, both do not have a substantial relationship for passenger arrivals (0.141) and passenger departures (0.115). The flow of unloading of goods has a significant relationship of (0.00). The greater the number of ship visits and the flow of unloading of goods, the higher the GDP Regional of the Processing Industry Sector, but the increasing number of passenger visits has no relation to the GDP Regional of the Processing Industry Sector.